(untitled) (ModaPalavra e-periódico, 2025)
This article proposes an approach to teaching the subject History of Fashion subject in Brazil for fashion design courses. Based on the classroom experience, it was possible to separate the history of fashion from the chronological chain, more commonly used in history subjects, and define a lesson plan based on the most significant events in fashion production in Brazil, since Colonial times. Three main axes were detected: textile production; the commercialization and dissemination of fashion; aesthetics and fashion creators. These axes connect and form a comprehensive content that permeates the entire constitution of Brazilian fashion. Based on these axes, a review of the available bibliography was presented with the main publications in the area relevant to the topics covered, punctuating their contributions to the best use of the discipline.